1996
DOI: 10.1021/ac960383c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Enantiomeric Composition of Chiral Amines Based on the Quenching of the Fluorescence of a Chiral Calixarene

Abstract: The synthesis of three chiral calixarene derivatives is described. One of these, an (S)-di-2-naphthylprolinol tetramer, is shown to exhibit significant ability to discriminate between enantiomers of 1-phenylethylamine (PEA) and norephedrine on the basis of the quenching of the (S)-di-2-naphthylprolinol fluorescence emission in chloroform. The chiral discrimination appears to arise from preorganization of the four (S)-di-2-naphthylprolinol substituents on the calixarene, which define a three-dimensional chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…Figure 5 illustrates the Stern-Volmer plots for the quenching of the fluorescence of calixarene L1 (0.7 µmol dm -3 in methanol), upon addition of 0% S-PA: 100% R-PA, 50% S-PA: 50% R-PA (racemic mix) and 100% S-PA: 0% R-PA respectively, at a concentration range of 0 -25mmol dm Previous results show that it is possible to discriminate between the enantiomers of chiral amines with appropriately arranged hydrogen bonding groups, chiral centres and quenching sites using suitably functionalised calix [4]arenes 14,15 . The position of the chiral centre relative to the hydrogen bonding groups and the aryl group in the guest molecule appears to be vitally important, illustrated by the fact that the calix [4]arene host L1 does not discriminate between enantiomers of phenylglycinol without an extra methylene spacer between the chiral centre and phenyl ring, while excellent discrimination is observed with phenylalaninol, with a methylene spacer 6 .…”
Section: Variation Of Stern-volmer Plot With Enantiomeric Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 illustrates the Stern-Volmer plots for the quenching of the fluorescence of calixarene L1 (0.7 µmol dm -3 in methanol), upon addition of 0% S-PA: 100% R-PA, 50% S-PA: 50% R-PA (racemic mix) and 100% S-PA: 0% R-PA respectively, at a concentration range of 0 -25mmol dm Previous results show that it is possible to discriminate between the enantiomers of chiral amines with appropriately arranged hydrogen bonding groups, chiral centres and quenching sites using suitably functionalised calix [4]arenes 14,15 . The position of the chiral centre relative to the hydrogen bonding groups and the aryl group in the guest molecule appears to be vitally important, illustrated by the fact that the calix [4]arene host L1 does not discriminate between enantiomers of phenylglycinol without an extra methylene spacer between the chiral centre and phenyl ring, while excellent discrimination is observed with phenylalaninol, with a methylene spacer 6 .…”
Section: Variation Of Stern-volmer Plot With Enantiomeric Compositionmentioning
confidence: 99%
“…In previous work it has been shown that calixarenes 9,10,11,12 and more recently fluorescent calixarenes 13,14,15 can discriminate between enantiomers. Here we present how solvent polarity has an effect not only on the extent of enantiomeric discrimination, but also on the wavelength at which discrimination occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Calixarenes for instance, which have been the subject of much synthetic developments, are making inroads into analytical and separation techniques. They will be useful not only for fluorescence based detection schemes for metal ions but for organics such as amines for instance [194].…”
mentioning
confidence: 99%
“…Sensing devices, which can differentiate between different enantiomers, would be a cheaper, easier way of carrying out this work. The McKervey group in colaboration with the Diamond group have been involved in studies carried out with (S)-di-napthylprolinolcalix [4]arene which has shown excellent chiral discrimination between the enantiomers of phenylglycinol, phenylethylamine and norephedrine 34 . The mechanism of transduction in this example is based on the fluorescence quenching of the napthylprolinol handles of the calixarene upon comlpexation with the R-enatiomer of phenylglycinol.…”
Section: Calixarenes As Chiral Recognition Devicesmentioning
confidence: 99%